External factors affecting performance
FACTORS AFFECTING PERFORMANCE Match type, pitch size, motivation, climate and luck all have an effect on performance... TEMPERATURE Differences in temperature can severely affect performance and increase risk of injury... ALTITUDE When competition will take place at high-altitude, players should be correctly prepared... CIRCADIAN (BIOLOGICAL) RHYTHMS & JETLAG The body's natural rhythms & travelling long distances can effect playing performance...